1998
DOI: 10.1139/f98-037
|View full text |Cite
|
Sign up to set email alerts
|

The impact of global positioning systems and plotters on fishing power in the northern prawn fishery, Australia

Abstract: The impact of global positioning systems (GPS) and plotter systems on the relative fishing power of the northern prawn fishery fleet on tiger prawns (Penaeus esculentus Haswell, 1879, and P. semisulcatus de Haan, 1850) was investigated from commercial catch data. A generalized linear model was used to account for differences in fishing power between boats and changes in prawn abundance. It was found that boats that used a GPS alone had 4% greater fishing power than boats without a GPS. The addition of a plotte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 4 publications
2
42
0
Order By: Relevance
“…Generalised linear regression approaches have been used to standardise average catches in the Gulf of Mexico prawn trawl fishery (Brunenmeister, 1984;Griffin et al, 1997), the Australian royal red prawn trawl fishery (Baelde, 1991) and to quantify the effects of global positioning systems (GPS) on average catches of tiger prawns in Australia's northern prawn fishery (Robins et al, 1998). Bishop et al (2000) further developed the analysis of Robins et al (1998) by using the generalised estimating equations (GEE) regression approach to account for spatial and temporal correlations in the data. In contrast to the regression approach, Salthaug and Godø (2001) used a model for standardisation based on the relative fishing power between pairs of vessels fishing at the same time and place to estimate fishing power relative to a 'standard' vessel; see also Hall and Penn (1979).…”
Section: Introductionmentioning
confidence: 99%
“…Generalised linear regression approaches have been used to standardise average catches in the Gulf of Mexico prawn trawl fishery (Brunenmeister, 1984;Griffin et al, 1997), the Australian royal red prawn trawl fishery (Baelde, 1991) and to quantify the effects of global positioning systems (GPS) on average catches of tiger prawns in Australia's northern prawn fishery (Robins et al, 1998). Bishop et al (2000) further developed the analysis of Robins et al (1998) by using the generalised estimating equations (GEE) regression approach to account for spatial and temporal correlations in the data. In contrast to the regression approach, Salthaug and Godø (2001) used a model for standardisation based on the relative fishing power between pairs of vessels fishing at the same time and place to estimate fishing power relative to a 'standard' vessel; see also Hall and Penn (1979).…”
Section: Introductionmentioning
confidence: 99%
“…At a broader level, it is possible to gain insights into variations in fishing power by comparing the performance of two or more vessels using different gear or practices. Robins et al (1998), for example, examined the impact of GPS and plotters on fishing power in an Australian prawn fishery. They found that vessels using GPS had 4% greater power than vessels without GPS.…”
Section: Measuring Fishing Power and Catchabilitymentioning
confidence: 99%
“…The addition of a plotter increased power by 7% over vessels without this equipment. Power increased by 12% when both pieces of equipment were used for at least three years (Robins et al 1998). In one of the few studies of longliner fishing power, Lin et al (1997) compared the performance of longliners using contemporary and traditional longline systems.…”
Section: Measuring Fishing Power and Catchabilitymentioning
confidence: 99%
“…Historical information may be acquired from administration registers, interview of skippers, owners, ship builders, net makers, ship chandlers, and so on (for example, Robins et al 1998), and on-going fleet surveys are inexpensive relative to ongoing surveys of the resource.…”
Section: Need To Acquire Data and Incorporate Into Analysesmentioning
confidence: 99%
“…Otherwise, changes in catch per unit effort that are due to variable catchability may be incorrectly concluded to be due to changes in abundance. Variable catchability can arise from patterns of availability and vulnerability, non-uniform recruitment and migration, and schooling behavior (Ricker 1975;Swain and Sinclair 1994;Arreguin-Sanchez 1996;Vignaux 1996a); technological changes in fishing gear and gear deployment (Dickson 1993;Rahikainen and Kuikka 2002) and changes in fishing strategies, target species and fleet dynamics (Vignaux 1996b;Gillis and Peterman 1998;Robins et al 1998;Walters 2003;Campbell 2004). This school of thought is in favor of focusing on reality and minimizing bias, above other considerations when modeling.…”
Section: Introductionmentioning
confidence: 99%